Keputusan migrasi di Indonesia - Riska Dwi Astuti (Jurnal Kebijakan Ekonomi dan Keuangan, 2023)
Purpose – This study aims to analyze individual characteristics and internal factors on affecting migration decision.Methods – Individual-level of 5698 respondents from the Indonesian Family Survey are analyzed using logistic and probit regressions.Findings – Marital status and number of household members are found to be negatively significant on affecting migration decision. Furthermore, the economic condition measured using income accumulation and debt at household level is statistically insignificant. Originality – This study is one of few research that use individual-level data to analyze migration in Indonesia. AbstrakTujuan – Penelitian ini bertujuan untuk menganalisis karakteristik individu atau faktor internal individu dalam mempengaruhi keputusan migrasi. Metode – Informasi di tingkat individu atas 5698 responden dari data Indonesian Family Life Survey (IFLS) dianalisis menggunakan regresi logit dan probit.Temuan – Status pernikahan dan jumlah anggota rumah tangga berpengaruh negatif signifikan terhadap keputusan individu bermigrasi. Di sisi lain, keadaan ekonomi rumah tangga yang dijelaskan dengan akumulasi pendapatan dan hutang rumah tangga tidak mempengaruhi keputusan migrasi.Orisinalitas – Penelitian ini merupakan satu dari sedikit analisis migrasi menggunakan data di tingkat individu di Indonesia